Woman with Turner syndrome and her child with acute leukemia (a case report) - Kitsera, N.; Dorosh, O.; Makukh, H. (PH Akademperiodyka, 2023)
Summary. Turner syndrome (TS) is a chromosomal condition that affects development in females. The case of TS in the mother whose child was diagnosed with acute leukemia at the age of 1.5 years is presented. FANCI gene in child was detected among 94 genes associated with hematologic malignancies. Acute lymphoblastic leukemia, common-B ІІ, L1, associated with t(12;21)(p13;q22), TEL/AML1 (ETV6/RUNX1) in a child was detected during a prophylactic examination. During the treatment of the baby, the mother had a second pregnancy, which ended in miscarriage at 8 weeks. Upon cytogenetic examination in the mother TS was revealed — mos45,Х[23]/46, ХХ[7], and the father’s karyotype was without abnormalities (46, ХУ). After chemotherapy, the child is in clinical-hematological remission. It could be suggested that chromosomal abnormalities in mother with TS may cause the chromosomal instability and hematological malignancy in offspring.